The morality of spin : virtue and vice in political rhetoric and the Christian right - Klemp, Nathaniel J., 1979- (Rowman & Littlefield Publishers, Inc., 2012)
The Morality of Spin explores the ethics of political rhetoric crafted to persuade and possibly manipulate potential voters. Based on extensive insider interviews with leaders of Focus on the Family, one of the most powerful Christian right organizations in America, Nathaniel Klemp asks whether the tactic of tailoring a message to a particular audience is politically legitimate or amounts to democratic malpractice. Klemp's nuanced assessment, highlighting both democratic vices and virtues of the politi.